Getarkan: An Interactive Game Slide Pull Food Chain to Improve Students’ Learning Outcomes in Elementary School - Ardana, I Nyoman Wahyu Adi; Rati, Ni Wayan (Thinking Skills and Creativity Journal, 2024)
The low interest of students in learning science is caused by several things such as the lack of innovative learning models and methods and the use of less interactive learning media. Fun learning media is needed to improve student learning outcomes. The purpose of this research is to develop a valid, practical, and effective interactive game learning media "Getarkan" to improve the learning outcomes of grade V elementary school students on food chain materials. This development research uses the ADDIE model which consists of five stages, namely, analyze, design, development, implementation, and evaluation. In this study, the type of data used consists of two, namely qualitative data and quantitative data. This study takes the subject of the interactive game media of Vibration, while the object taken is the validity, practicality, and effectiveness of the interactive game media of Vibration. The data collection methods used are rating scales and student learning outcome tests. The results of the study show that the interactive game media of Getarkan received validity from experts with a very high category, and the practicality assessed by students and teachers received very high scores. To test the effectiveness of media on learning outcomes, interactive media was declared effective in improving student learning outcomes on food chain materials. Because there is a difference before and after learning using interactive media.